Effect of Drying Method on Antioxidant Activity and Total Flavonoid Content of Java Tea Crude Drug (Orthosiphon aristatus) - Daffa Purnomo; Alvina Yulianti Putri; Haikal Muhammad Hisyam; Rizka Rimatunnisa; Dania Regita Indriani; Pasca Ryan Adinda; Yeti Rusmiati Hasanah; Alwani Hamad (Research in Chemical Engineering, 2023)
Java tea (Orthoshipon aristatus) is a medicinal plant with antioxidant properties due to its polyphenols, flavonoids, phenolic acids, terpenoids, and sinensetin content. Numerous diseases, including hepatitis, diabetes, hypertension, and others, are commonly treated with Java tea. These bioactive compounds are unstable and readily degraded by oxygen, heat, and light. Inappropriate dehydration techniques may compromise the quality of the bioactive compounds in herbal Java tea crude drugs by damaging the bioactive compounds. Consequently, this study aims to determine the effect of various drying methods on the antioxidant activity and Total Flavonoid Content (TPC) of the crude drug of Java tea. In addition, the physical properties, including water content and hygroscopicity, are investigated. The method employs cabinet drying at 30 and 70 degrees Celsius, infrared drying, and sun drying. The results demonstrated that the crude drug dried in a cabinet at 30oC had the maximum flavonoid content (61.03±5.35mg QE/g) and moisture content (15.12±0.27%). The antioxidant activity of DPPH free radical scavenging and Ferri Reduction Antioxidant Power (FRAP) of Java tea from infrared drying was lower than other drying methods. All samples were non-hygroscopic powders. Consequently, the dehydration method significantly affects the antioxidant activity, TFC levels, and physical properties of the crude drug of Java tea.